Mechanism of neél order switching in antiferromagnetic thin films revealed by magnetotransport and direct imaging - Baldrati, L.; Gomonay, Olena; Ross, Andrew; Filianina, M.; Lebrun, Romain; Ramos, Rafael; Leveille, C.; Fuhrmann, F.; Forrest, T. R.; Maccherozzi, F.; Valencia, Sergio; Kronast, F.; et al. (Physical Review Letters, 2019)
We probe the current-induced magnetic switching of insulating antiferromagnet-heavy-metal systems, by electrical spin Hall magnetoresistance measurements and direct imaging, identifying a reversal occurring by domain wall (DW) motion. We observe switching of more than one-third of the antiferromagnetic domains by the application of current pulses. Our data reveal two different magnetic switching mechanisms leading together to an efficient switching, namely, the spin-current induced effective magnetic anisotropy variation and the action of the spin torque on the DWs.
CRIS-Team Scopus Importer:2023-03-27